Association of inflammatory burden index with prognosis as well as stroke-associated pneumonia in non-surgical patients with spontaneous intracerebral hemorrhage - Wang, Xinyu; He, Lingqian; Cui, QiQi; Zhao, Jiapeng; Song, Juexian (Frontiers in Neurology, 2025)
AimTo assessment the new biomarker, the inflammatory burden index (IBI) and their correlations with clinical outcome as well as stroke-associated pneumonia (SAP) of ICH patients.MethodsPatients diagnosed as spontaneous intracranial hemorrhage (SICH) were retrospectively screened from December 2018 to December 2022. The IBI was formulated as C-reactive protein×neutrophils/lymphocytes. In addition, systemic-inflammatory indices including ratios of neutrophil-to-lymphocyte (NLR), monocyte-to-lymphocyte (MLR), platelet-to-lymphocyte (PLR),and patelet-to-neutrophil (PNR), systemic immune-inflammation index (SII), and systemic inflammation response index (SIRI) on admission also were calculated. The primary outcome measure was 90-day functional outcome and the occurrence of SAP, with an mRS 3–6 score representing a unfavorable outcome. We used ROC curves to evaluate the diagnostic value of these differences. Univariate and multivariable analyses was conducted to identify the factors independently associated with 3 months unfavorable functional outcomes and stroke-associated pneumonia.ResultsA total of 209 patients were enrolled, of which 144 (68.9%) had unfavorable 90-day functional outcome, and 89 (42.1%) ICH patients developed SAP. Elevated IBI is an independent predictor for both stroke-associated pneumonia (SAP) and unfavorable 3-month outcomes in acute ICH patients, and showed a good predictive ability for SAP (AUC = 0.811, p < 0.001) and poor prognosis at 3 months (AUC = 0.745, p < 0.001).ConclusionInflammatory biomarker index (IBI) are predictive of 90-day functional outcome and the SAP occurrence in patients with ICH.